Posted by **Anonymous** on Thursday, May 17, 2012 at 2:51pm.

Suppose f(x)=cos x - sin x and g(x)=cos x + sin x. Explain why the graph of (fxg)(x) is equivalent to the graph of h(x)=cos x after it has been horizontally compressed by a factor of 1/2. Thanks so much...

## Answer this Question

## Related Questions

- trig function - Suppose f(x)=cos x - sin x and g(x)=cos x + sin x. Explain why ...
- trig function - Suppose f(x)=cos x - sin x and g(x)=cos x + sin x. Explain why ...
- trig function - Suppose f(x)=cos x - sin x and g(x)=cos x + sin x. Explain why ...
- trig and combine function - Suppose f(x)=cos x - sin x and g(x)=cos x + sin x. ...
- TRIG! - Posted by hayden on Monday, February 23, 2009 at 4:05pm. sin^6 x + cos^6...
- trig - The expression 4 sin x cos x is equivalent to which of the following? (...
- trig - Reduce the following to the sine or cosine of one angle: (i) sin145*cos75...
- tigonometry - expres the following as sums and differences of sines or cosines ...
- Mathematics - Trigonometric Identities - Let y represent theta Prove: 1 + 1/tan^...
- Precal - I do not understand how to do this problem ((sin^3 A + cos^3 A)/(sin A...